Control-IQ Technology Positively Impacts Patient Reported Outcome Measures and Glycemic Control in Youth with Type 1 Diabetes in a Real-World Setting. (12th April 2023) - Zuijdwijk, Caroline; Courtney, Jennilea; Mitsakakis, Nicholas; Hayawi, Lamia; Sutherland, Stephanie; Newhook, Dennis; Ahmet, Alexandra; Goldbloom, Ellen B.; Khatchadourian, Karine; Lawrence, Sarah
Abstract : Objective . To determine the impact of the t:slim X2 insulin pump with Control-IQ technology on the quality of life and glycemic control in youth with type 1 diabetes (T1D) and their parents in a real-world setting. Research Design and Methods . We conducted a single-center, prospective study on pediatric patients (6–18 years old) with T1D using a Tandem t:slim X2 pump and initiating Control-IQ technology as part of routine care. Youth (≥8 years) and parents completed validated patient-reported outcome measures (PROMs) at baseline and the end of the study (16 weeks). Glycemic control measures were recorded at baseline and every 4 weeks until the end of the study. Results . Fifty-nine youth participated; the median (IQR) age was 13.8 (11.1, 15.7) years, and T1D duration was 6.3 (3.1, 8.4) years. INSPIRE scores (evaluating expectations (baseline) and impact (post) of Control-IQ technology) were favorable, unchanged at the end of the study for youth, and lower for parents (p = 0.04 ). Other PROM scores improved by the end of the study with mean (95% CI) differences for youth and parents, respectively, as follows: Diabetes Impact and Device Satisfaction (DIDS) Scale Diabetes Impact −1.08 (−1.51, −0.64) (p < 0.001 ) and −1.41 (−1.96, −0.87) (p < 0.001 ); DIDS Scale Device Satisfaction +0.43 (0.11, 0.74) (p = 0.01 ) and +0.58 (0.31, 0.85) (p < 0.001 ); Hypoglycemia Fear Survey −4.41 (−7.65, −1.17) (p = 0.01 ) and −7.64 (−11.66, −3.62) (p < 0.001 ); and WHO-5 Well-Being Index +5.10 (−1.40, 11.6) (p = 0.12 ) and +9.60 (3.40, 15.8) (p = 0.003 ). The mean time in range increased from 52.6% at baseline to 62.6% (p < 0.001 ) at 4 weeks, sustained to 16 weeks. Conclusions . Initiation of Control-IQ technology in a real-world setting significantly reduced the impact of diabetes on daily life while simultaneously improving glycemic control. Trial Registration . This trial is registered with ClinicalTrials.gov Identifier NCT04838561 (https://www.clinicaltrials.gov/ct2/show/NCT04838561?term=Control-IQ&cond=Type+1+Diabetes&cntry=CA&draw=2&rank=1 ).